Bacterial flora of farmed mud crab, Scylla serrata (Forskal, 1775) and farm environments in Kerala, India - Lalitha, Kuttanappilly Velayudhan elayadom; Nirmala, Thampuran (Indian Journal of Fisheries, 2012)
The microflora associated with mud crab Scylla serrata collected from farms located in Kerala, India were investigated. The microbial load and types of bacteria associated with farm water, sediment and crabs were monitored. The mean mesophilic count of 5.67 log10 cfu g-1 in farmed fresh crab indicates acceptable crab quality. The levels of enterococci and faecal coliforms in farmed mud crab were high. The microbial groups, most commonly isolated from crab meat were Vibrio, Enterobacteriaceae, Moraxella, Acinetobacter, Pseudomonas/Shewanella, Micrococcus and Bacillus. The percentage composition of various genera in crab meat varied between farms. The study reports a diverse array of bacterial species, including several potential human pathogens such as Vibrio fluvialis, Vibrio hollisae, Vibrio mimicus, Aeromonas veronii biovar sobria, Aeromonas caviae and Aeromonas jandaei from edible crabs. Owing to the potential hazard of these pathogenic bacteria, it is necessary to put more emphasis on hygienic handling of farmed crab. This study confirms that farmed crab carry significant numbers of motile aeromonads, capable of growth at low temperature. Immediate icing of harvested crabs is essential to improve the microbiological stability.